2019
DOI: 10.1186/s42269-019-0046-5
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Aspergillus tamarii NRC 3 biomass as a biosorbent for removal and recovery of heavy metals from contaminated aqueous solutions

Abstract: Background: Biomass produced as a byproduct from the β-mannanase production process by Aspergillus tamarii NRC 3was evaluated as a biosorbent for the removal and recovery of some heavy metal ions.Results: Under optimal conditions, the isolated strain recorded the highest β-mannanase activity (31.88 Uml −1 ). Thus, the biomass produced from mannanase production process as a byproduct was evaluated as a biosorbent for the removal and recovery of some heavy metal ions from aqueous solutions and an industrial wast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 31 publications
2
9
0
Order By: Relevance
“…and A. niger . In similar biosorption studies, it has been reported that maximum Cu (II) and Co (II) uptake by Aspergillus tamarii NRC 3 biomass was 92.40 and 60%, respectively, in a solution comprising 5 g of A. tamarii wet biomass ( Saad et al, 2019 ). It has also been observed that the removal capacity differs with fungal species.…”
Section: Factors Affecting Bioremoval Of Copper and Cobalt Ions By Fimentioning
confidence: 83%
See 3 more Smart Citations
“…and A. niger . In similar biosorption studies, it has been reported that maximum Cu (II) and Co (II) uptake by Aspergillus tamarii NRC 3 biomass was 92.40 and 60%, respectively, in a solution comprising 5 g of A. tamarii wet biomass ( Saad et al, 2019 ). It has also been observed that the removal capacity differs with fungal species.…”
Section: Factors Affecting Bioremoval Of Copper and Cobalt Ions By Fimentioning
confidence: 83%
“…Aspergillus tamarii NRC 3 obtained from contaminated Egyptian soil was used as a biosorbent for the bioremoval and bio-recovery of heavy metals ( Saad et al, 2019 ). From the findings, live A. tamarii NRC 3 biomass could absorb 90.94% Cu (II), 29.13 of Pb (II), 60% of Co (II), 40% of Ni (II), 34.47% of Fe (II), and 11.45% of Cr (II) respectively.…”
Section: Potential Filamentous Fungi Species and Their Properties In mentioning
confidence: 99%
See 2 more Smart Citations
“…Lab-scale and greenhouse experiments validate soil HM mycoremediation performance [ 24 , 31 , 39 ]. Similarly, effective recovery of HMs from contaminated water by fungi as biosorbents has also been demonstrated at small-scales [ 45 , 46 , 47 , 48 ]. Fungal biosorbents were extensively studied by previous researchers [ 46 , 47 , 48 , 49 , 50 , 51 , 52 ].…”
Section: Introductionmentioning
confidence: 99%